Near Earth asteroid resource utilisation for large in-orbit reflectors. (August 2016) - McInnes, Colin R.
Abstract: The resources offered by the family of near Earth asteroids could provide bulk materials to support future space science ventures, both crewed missions and space-based astronomy. Using low-energy transfer trajectories small near Earth asteroids could be captured directly, or their material resources returned to Earth orbit or the Lagrange points. With novel fabrication methods, such as additive layer manufacturing, large-scale space structures including optical and radio telescopes could in principle be assembled from such resources. Indeed, with bulk materials readily available, very large numbers of structures could be fabricated in-situ for interferometry applications.